Recent advances of cementing technologies for ultra-HTHP formations. (11th November 2021) - Cai, Wenjun; Deng, Jingen; Luo, Ming; Feng, Yongcun; Li, Jing; Liu, Qiang
Ultra-high-temperature-high-pressure (ultra-HTHP) formations are usually those formations having a temperature over 200°C and a pore pressure over 140 MPa. With the growing demand for oil and gas resources all over the world, ultra-HTHP formations are more frequently encountered during exploration and development activities. Compared with conventional HTHP wells, it is much more difficult to solve the issues of unstable cement slurry and poor displacement efficiency in the ultra-HTHP wells. Consequently, fluid loss, gas channelling, and other complexities are commonly encountered during cementing in the ultra-HTHP formations. To provide a reference for solving these issues, this work reviews and discusses the advances and applications of a series of cement materials, tools, and technologies developed in the last decade. The work also indicates that these advances cannot overcome all cementing challenges in the ultra-HTHP formations with complex downhole conditions. In short, many achievements have been done in ultra-HTHP cementing technologies, and many improvements remain to be done ahead. [Received: April 26, 2020; Accepted: November 15, 2020]